PERAN PUSTAKAWAN DALAM MENGEMBANGKAN KUALITAS LAYANAN DI PERPUSTAKAAN UNIVERSITAS MUHAMMADIYAH PONTIANAK - Christoporus Dasli Juang; Antonius Totok Priyadi (Universitas Tanjungpura, 2020)
AbstractThis study discusses about the efforts of librarians in developing the quality of library services at the University of Muhammadiyah Pontianak. This study was to find out how the efforts of librarians and library managers in developing service quality and the obstacles encountered during carrying out. Collecting data used were observation, interviews, and documentation. The informants in this study which are the librarians of the place where the research was conducted. The results of the analysis found that the quality of services provided by the library was good in terms of general services such as circulation, references, electronics, and membership services, but not yet in terms of college standards library. It can be seen from some obstacles that are still faced such as the lack of attention from the related stakeholders. The librarians is trying to build better communication with superiors of educational institutions and also has made plans to develop quality services such as building Muhammadiyah Corner, adding new collections, room improvements, and together with the head of library planning to add human resources to manage the library.Keywords: librarians, quality, services, library